Varieties of capitalism and growth regimes: the role of income distribution - Jan Behringer; Till van Treeck (Hans-Böckler-Stiftung, Macroeconomic Policy Institute (IMK), Forum for Macroeconomics and Macroeconomic Policies (FMM), 2017)
This article brings together the varieties of capitalism and the growth model approaches to comparative political economy to analyze the macroeconomic implications of changes in income distribution. In the decades before the financial crisis, coordinated market economies (CMEs) and liberal market economies (LMEs) developed different but unsustainable growth models which resulted in global current account imbalances. We analyze the relative importance of wage coordination and income distribution in explaining the emergence of global imbalances. We argue that strongly rising top income shares contributed to the decline in household saving and current account balances in major LMEs, whereas pronounced falls in the wage share contributed to the weakness of domestic demand and rising current account balances in CMEs. Wage coordination affected current account balances both directly and, more importantly, indirectly through its effects on income distribution. We test the argument for a sample of 18 industrialized countries over the period 1981-2007.
Keywords: 330; Functional income distribution; personal income distribution; wage coordination; varieties of capitalism; growth models